A new shrimp of the genus Odontozona Holthuis, 1946 (Decapoda: Stenopodidea: Stenopodidae) from a submarine cave of the Ryukyu Islands, Indo-West Pacific - Saito, Tomomi; Fujita, Yoshihisa (Zootaxa, 2022)
A new species of the stenopodid shrimp genus Odontozona Holthuis, 1946 is described and illustrated on the basis of single specimen recently collected from a submarine cave at Shimoji-jima Island, Miyako Island Group, Ryukyu Islands, southwestern Japan. Odontozona ganzu sp. nov. appears to be unique within the genus Odontozona by lacking transverse row of posterior small spines on sixth pleuron. General morphology of the new species is also similar to O. stigmatica Saito, Okuno & Anker, 2017 described from Ishigaki-jima Island, Ryukyu Islands, West Pacific, but differs from it by a combination of morphological characters, viz., lacking the cincture of small spines on the posterior margin of the carapace, the distinct transverse carina on the third pleuron, as well as the lateral teeth of the uropodal endopod. This study increases the total number of the described species in the genus Odontozona to 23, 11 of which occur the Indo-West Pacific.